2012
DOI: 10.1097/ajp.0b013e3182453e1b
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Mobilization of the Cervical Spine for the Treatment of Chronic Neck Pain

Abstract: These preliminary results demonstrate the safety of a novel computerized mobilization of the cervical spine. In addition, the data suggest that this method is effective in increasing CROM and in alleviating NP and associated headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…In one patient, a true vertigo episode occurred probably due to benign positional vertigo. Dizziness was more common in this trial, as compared with a previous trial [5], as three‐dimensional space mobilizations can more effectively trigger vestibular semicircular canal activation. As a result, it can be suggested that avoiding excessive pressure on the scalp by the cradle, excluding patients with dizziness and vertigo, and limiting the angular velocities applied by the Occiflex device could reduce these minor side effects.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In one patient, a true vertigo episode occurred probably due to benign positional vertigo. Dizziness was more common in this trial, as compared with a previous trial [5], as three‐dimensional space mobilizations can more effectively trigger vestibular semicircular canal activation. As a result, it can be suggested that avoiding excessive pressure on the scalp by the cradle, excluding patients with dizziness and vertigo, and limiting the angular velocities applied by the Occiflex device could reduce these minor side effects.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, new research into the mechanism of NP syndromes and clinical trials evaluating unexplored innovative therapeutic interventions are needed. In a previous trial, computerized mobilization of the cervical spine confined to the sagittal plane was shown to be safe and potentially effective [5]. The improvement observed in this trial was reflected in both objective physiological measures and reliable questionnaires.…”
Section: Introductionmentioning
confidence: 67%
“…In a previous pilot trial, we showed that computerized mobilization of the cervical spine confined to the sagittal plane is a safe and potentially effective treatment of CNP. Specifically, the treatment yielded improvements in objective physiological measures, as well as in patients' self-reports of their condition, as reflected in reliable questionnaires [5,6]. In a second pilot trial we showed that a 6-week treatment course of biweekly computerized mobilization with a sequence of movements in the sagittal, coronal and horizontal planes is followed by significant reduction of CNP, improvement in neck range of motion, and reduction in joint position error [7].…”
Section: Introductionmentioning
confidence: 82%
“…Computerized mobilization treatment was performed with the Occiflex device ( Figure 1) [6,7]. This device was developed to optimize neck mobilization.…”
Section: Computerized Mobilizationmentioning
confidence: 99%
See 1 more Smart Citation